Leaf Functional Traits Vary in Urban Environments: Influences of Leaf Age, Land-Use Type, and Urban–Rural Gradient - Su, Yuebo; Cui, Bowen; Luo, Yunjian; Wang, Jia; Wang, Xuming; Ouyang, Zhiyun; Wang, Xiaoke (Frontiers in Ecology and Evolution, 2021)
An increasing number of studies have focused on the response and adaptation of plants to urbanization by comparing differences in leaf functional traits between urban and rural sites. However, considerable uncertainties remain because differences in land-use type have not frequently been taken into account when assessing the effect of urbanization on leaf traits. In this study, we sampled the needles of Chinese pine (Pinus tabuliformis Carr.) in areas with three land-use types (roadsides, parks, and neighborhoods) along an urban–rural gradient in Beijing, China to determine the effect of urbanization on leaf functional traits. There were significant differences in the values of leaf functional traits between the needles of the current and previous year and across land-use types. Pines growing on roadsides had leaves with smaller length, width, and area, as well as lower stomatal density, compared with those growing in parks and neighborhoods. This implies that on roadsides, plant capacity to acquire resources (e.g., light and carbon dioxide) was degraded. Stomatal density, leaf width, and leaf P concentration increased with increasing distance from the city center, while leaf K concentration decreased with increasing distance from the city center. Importantly, there were significant differences in the urban–rural gradient of leaf functional traits between leaves of different ages, and across land-use types. Leaf age was the most important factor influencing leaf nutrient traits, while land-use type was the most important factor influencing leaf morphological traits in urban environments. Thus, considering the effects of the plant characteristic and land-use type on traits is important for assessing the urban–rural gradients of plant functional traits.